ENGLISH TEACHING TECHNIQUES USED BY TEACHERS IN TEACHING WRITING DESCRIPTIVE TEXT TO STUDENTS OF SMK TELKOM MEDAN - Sarifah Siregar; Berlin Sibarani (GENRE JOURNAL : Journal of Applied Linguistics of FBS Unimed, 2020)
This research was dealt with teaching techniques used by teachers in teaching writing descriptive text. The objective of this study were (1) to analize the teaching techniques used by teachers in teaching writing descriptive text to students at SMK Telkom Medan and (2) to find out  the reasons of doing that way in the process of teaching writing descriptive text to students. The subject of the study was the teachers of SMK Telkom Medan. A descriptive qualitative design was used in this study.  The data were collected by recording the utterances of teacher. The data were analyzed by data condensation, data display, conclusion drawing/verification. There were three types of teaching techniques used by teachers in teaching writing descriptive text namely Collaborative Writing Technique, Graphic Organizer Technique, and Cubing Technique. Based on the result, it may be concluded that : (1) from three techniques above 50% teacher used collaborative writing technique, 50% teacher used graphic organizer technique and there was no teachers using cubing technique in SMK Telkom Medan. (2) For the reasons of doing that way in process of teaching writing descriptive text to students. There were two reasons, building team work and helping critical thinking.